Characteristics and models of China’s tourism poverty alleviation from the perspective of IRT framework - LI Yanqin, CUI Jiaqi, SHI Jiawei (Ziyuan Kexue, 2023)
[Objective] This study aimed to provide a guidance and theoretical support for the practice of rural revitalization by examining China’s tourism poverty alleviation experience. [Methods] Based on the theoretical framework of integrated rural tourism (IRT), this research analyzed the 90 Chinese cases in the World Tourism Alliance (WTA) best practice in poverty alleviation through tourism cases from 2018 to 2020 by the content analysis. NVivo11 pro was used for text processing and encoding of structured data. [Results] (1) We converted the IRT framework into a SQEI framework that is composed of speed, quality, extrinsic, and intrinsic dimensions, and established a tourism development model system of 4 categories and 10 subcategories; (2) Among the models of tourism poverty alleviation in China, the “extrinsic-quality” model of “enterprise + employment” accounted for the largest number and was the most widely distributed; (3) With regard to the spatial distribution of tourism poverty alleviation models, eastern China mainly adopted the “intrinsic-quality” model of “cooperative + employment”, central China mainly adopted the “extrinsic-speed” model of “village enterprise + industry”, and western China mainly adopted the “extrinsic-speed” model of “enterprise + industry”; (4) There were two paths for the evolution of tourism development models: the vertical evolution path, and the horizontal evolution path. The horizontal evolution path seeks to balanced development according to local conditions, while in the vertical path, the “cooperative + employment” model develops into the “enterprise + industry” model through the “village enterprise + industry” model in eastern China, or the “external enterprise + employment” model in western China. [Conclusion] (1) The SQEI poverty alleviation framework based on the IRT framework fits China’s situation better, and is a more suitable analytical framework for China’s tourism poverty alleviation experience; (2) Aiming to benefit the development of the poor population, the Chinese government mobilized various forces, and therefore China’s tourism poverty alleviation practice is characterized by government-led, external assistance, and high quality poverty alleviation; (3) In the evolution of tourism development models, the balanced development model of “enterprise + household + cooperative” is the ideal development model. In order to implement the rural revitalization strategy based on the effects of poverty alleviation, regions need to learn from their existing successful experience and use the advantages of tourism development to prevent poverty, be aware that the revitalization of a rural area should take into consideration its local conditions, and build a co-creation mechanism with multiple stakeholders in tourism development.